If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 = 19 + -4y Solving 1 = 19 + -4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4y' to each side of the equation. 1 + 4y = 19 + -4y + 4y Combine like terms: -4y + 4y = 0 1 + 4y = 19 + 0 1 + 4y = 19 Add '-1' to each side of the equation. 1 + -1 + 4y = 19 + -1 Combine like terms: 1 + -1 = 0 0 + 4y = 19 + -1 4y = 19 + -1 Combine like terms: 19 + -1 = 18 4y = 18 Divide each side by '4'. y = 4.5 Simplifying y = 4.5
| 4(v-4)-6=-7(-2v+1)-v | | 11x^2+2x+16+(-2x^2)+x+-2= | | 15-(2x+7)= | | -9(5y+3)= | | 12x+10=130 | | u-u+3u-3u+3u=6 | | 7x+6=5x-(3-2x)+9 | | -2(c-5)+3c=4(265-c) | | 7x-20+-10x=11 | | x^2+1.78x^2=3025 | | x+6x^2=16 | | 3.64=x/8 | | 44-2x=9-7x | | 5y-4y=18 | | 8+5*2+3*4=128 | | -5(n-s)= | | 100[0.02(n+6)]= | | 2(x-3)-4x=36 | | 10y-y-5y-6y=8 | | 10-2b=24 | | -60=-15 | | 5(2x-4)-2(x+1)-17x= | | -4(4u-1)+4u=9+3(2u-5) | | (-7x^2y)(-10x^3y^5)= | | 5b-20=15 | | 15q-14q=20 | | (-.75)(-8x)(1.3)(4y)(1)=c | | -3(d-7)+9=27 | | 2x^2+10-600=0 | | 2s+s=15 | | 3.6(x+9)+4.9x= | | -6=z/5-3 |